Radiation damage within nucleoprotein complexes studied by macromolecular X-ray crystallography - Bury, C; Carmichael, I; McGeehan, J; Garman, E (Elsevier, 2016)
In X-ray crystallography, for the determination of the 3-D structure of macromolecules, radiation damage is still an inherent problem at modern third generation synchrotron sources, even when utilising cryo-crystallographic techniques (sample held at 100 K). At doses of just several MGy, at which a typical diffraction dataset is collected, site-specific radiation-induced chemical changes are known to manifest within protein crystals, and a wide body of literature is now devoted to understanding the mechanisms behind such damage. Far less is known regarding radiation-induced damage to crystalline nucleic acids and the wider class of nucleoprotein complexes during macromolecular X-ray crystallography (MX) data collection. As the MX structural biology community now strives to solve structures for increasingly larger and complex macromolecular assemblies, it essential to understand how such structures are affected by the X-ray radiation used to solve them. The purpose of this review is to summarise advances in the field of specific damage to nucleoprotein complexes and to present case studies of MX damage investigations on both protein-DNA (C.Esp1396I) and protein-RNA (TRAP) complexes. To motivate further investigations into MX damage mechanisms within nucleoprotein complexes, current and emerging protocols for investigating specific damage within Fobs(n)−Fobs(1) electron density difference maps are discussed.